Nanoslurry and method for preparing same, battery separator and method for producing same, and battery

The introduction of a nanos rally with ceramic materials, one-dimensional nano materials, and linear hydrophilic polymers addresses the non-uniform coating issue in lithium-ion battery separators, enhancing stability and safety.

JP2025503266AActive Publication Date: 2025-01-30SHENZHEN SENIOR TECH MATERIAL +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024545002
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-02-21
Publication Date
2025-01-30
Estimated Expiration
2042-02-21

Smart Images

  • Figure 2025503266000001_ABST
    Figure 2025503266000001_ABST
Patent Text Reader

Abstract

The present invention provides a nanoslurry and a preparation method thereof, a battery separator and a manufacturing method thereof, and a battery, wherein the nanoslurry includes a dispersant, a ceramic material, a one-dimensional nanomaterial, a linear hydrophilic polymer, and an adhesive, and the mass ratio of the one-dimensional nanomaterial to the ceramic material is within the range of 0.01% to 20%, and the particle size of the ceramic material is within the range of 5 to 500 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of batteries, in particular to a nanoslurry and a method for preparing the same, a battery separator and a method for fabricating the same, and a battery. [Background technology]

[0002] lithium ion The battery separator is one of the important components of a lithium-ion battery, and its performance depends on the lithium ion This has a very significant impact on the overall performance of the battery, and lithium ion It is one of the key technologies limiting the development of batteries. ion As the application field of batteries continues to expand and the impact of lithium-ion electric products on people's lives deepens, ion The demands on battery performance are also becoming higher. ion In order to meet the requirements of battery development, the separator is ion As an important component of batteries, lithium ions are not only chemically stable and inexpensive to manufacture, but also help improve the safety performance of lithium-ion batteries. ion This is an important trend in battery development.

[0003] In the prior art, lithium ion The battery separator may include a base film and a coating covering at least one surface of the base film, and a coating slurry may be prepared based on ceramic particles; however, the ceramic particle surfaces are prone to problems of agglomeration of the ceramic particles, resulting in poor uniformity of the coating surface, which in turn affects the subsequent bonding of the electrodes in the battery assembly. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a nano-slurry and its preparation method, a battery separator and its fabrication method, and a battery, in order to solve the problem of surface agglomeration of ceramic particles. [Means for solving the problem]

[0005] According to a first aspect, the present invention provides a separator comprising a dispersion medium, a ceramic material, a one-dimensional nanomaterial, a linear hydrophilic polymer, and an adhesive. Octopus The present invention provides a nanoslurry for coating, in which the mass ratio of the one-dimensional nanomaterial to the ceramic material is within the range of 0.01% to 20%, the water content in the dispersion medium is 90 wt% or more, and the particle diameter of the ceramic material is within the range of 5 to 500 nm.

[0006] Optionally, the linear hydrophilic polymer is attached to the one-dimensional nanomaterial and linked to the ceramic material.

[0007] Optionally, the mass ratio of the linear hydrophilic polymer to water in the dispersion medium is within the interval of 0.01% to 0.1%.

[0008] Optionally, the molecular weight of the linear hydrophilic polymer is within the interval of 1000 g / mol to 10000 g / mol.

[0009] Optionally, the linear hydrophilic polymer comprises an amine hydrophilic polymer.

[0010] Optionally, the linear hydrophilic polymer is The polymer contains at least one of polyacrylamide and polyethyleneimine.

[0011] Optionally, the diameter of the one-dimensional nanomaterial is within the interval of 1 to 50 nanometers and the length of the one-dimensional nanomaterial is within the interval of 100 to 1000 nanometers.

[0012] Optionally, the mass ratio of the adhesive to the ceramic material is in the interval range of 1% to 10%.

[0013] Optionally, the adhesive is The adhesive layer includes at least one of polyvinyl alcohol, lithium polyacrylate, sodium carboxymethyl cellulose, and styrene butadiene rubber.

[0014] According to a second aspect, the present invention provides a method for preparing a nanoslurry according to the first aspect and its alternative solutions, said method comprising: A step of dispersing a ceramic material in a dispersion medium having a water content of 90 wt % or more to obtain a ceramic dispersion; Dispersing a one-dimensional nanomaterial in the ceramic dispersion to obtain a predetermined dispersion; adding a linear hydrophilic polymer to said predetermined dispersion to obtain a predetermined solution; Adding an adhesive to the predetermined solution to obtain a nanoslurry.

[0015] Optionally, after adding a linear hydrophilic polymer to the selected dispersion, the preparation method further comprises: The method further comprises dispersing the linear hydrophilic polymer in the selected dispersion by homogenization at a selected pressure and / or stirring at a selected speed to attach the linear hydrophilic polymer to the one-dimensional nanomaterial.

[0016] According to a third aspect, the present invention provides a battery separator comprising a base film and a coating, the coating is formed by applying a predetermined nano-slurry to at least one surface of the base film; The predetermined nanoslurry is a nanoslurry according to the first aspect and its alternative solutions or a nanoslurry prepared by the preparation method according to the second aspect.

[0017] According to a fourth aspect, the present invention provides a battery separator, comprising a base film and a coating, the coating comprising a ceramic material, a one-dimensional nano material, and a linear hydrophilic polymer, the mass ratio of the one-dimensional nano material to the ceramic material being within the interval of 0.01% to 20%, the particle size of the ceramic material being within the interval of 5 to 500 nm, and the linear hydrophilic polymer. of , the one-dimensional nanomaterial Attach to Connect to the ceramic material.

[0018] According to a fifth aspect, the present invention provides a battery comprising a battery separator according to the third or fourth aspect. Effect of the Invention

[0019] In the nanoslurry and its preparation method, battery separator and its manufacturing method, and battery provided by the present invention, a one-dimensional nanomaterial is introduced into a ceramic material to reduce the surface energy of the ceramic material, thereby reducing the surface roughness of the formed coating, and at the same time, a linear hydrophilic polymer is used to further reduce the surface roughness, whereby the linear hydrophilic polymer acts as a bridge between the one-dimensional nanomaterial and the ceramic material, completely binding the two, further fully reducing the aggregation tendency of the ceramic material, and further reducing the surface roughness of the formed coating. The introduction of the linear hydrophilic polymer can also contribute to avoiding the sedimentation of the slurry and improving the stability of the slurry.

[0020] In addition, based on research into the slurry state, it can be found that the selection of the mass of the one-dimensional nanomaterial has a certain correlation with the final slurry state (e.g., viscosity), and thus the present invention creatively discovers and utilizes this finding, selecting the mass ratio of the one-dimensional nanomaterial to the ceramic material in the range of 0.01% to 20%, effectively ensuring that the slurry can be easily applied. [Brief description of the drawings]

[0021] In order to more clearly describe the embodiments of the present invention or the solutions of the prior art, the drawings that need to be used in the description of the embodiments or the prior art are briefly described below. Of course, the drawings described below are some embodiments of the present invention, and those skilled in the art can think of other drawings based on these drawings without creative efforts. [Figure 1] 1 is a flow chart of a method for preparing nanoslurry in one embodiment of the present invention. [Diagram 2] 2 is a flow chart of a method for making a battery separator in one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, the technical solutions of the present invention will be described clearly and completely with reference to the drawings of the embodiments of the present invention, and it should be understood that the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments thereof, and all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative labor, all belong to the protection scope of the present invention.

[0023] In the description of the present invention, the orientations or positional relationships indicated by terms such as "upper", "lower", "top", "bottom", "lower surface", and "top surface" are orientations or positional relationships shown in the drawings, and are terms used only for the convenience and simplification of the description of the present invention. These terms are not terms that indicate or imply that the devices or components shown necessarily have a specific orientation or are constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention.

[0024] In the description of the present specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as terms indicating or teaching the relative importance or implying the number of technical features shown. Thus, a feature qualified by "first" or "second" may explicitly or implicitly include one or more of the said features.

[0025] In the description of the present invention, "plurality" means many, for example, two, three, four, etc., unless expressly limited otherwise.

[0026] In the description of the present invention, unless otherwise clearly defined and limited, the term "connected" should be interpreted broadly, for example, fixedly connected, detachably connected, or connected to be integrated, mechanically connected, electrically connected, or connected to be communicatively connected to each other, directly connected, indirectly connected through an intermediate medium, or connected to be in communication between two components or to be in an interactive relationship between two components. Those skilled in the art can understand the specific meaning of the above terms in the present invention according to the actual situation.

[0027] The technical solutions of the present invention are described in detail below using specific embodiments. Some of the following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be repeatedly described in some of the embodiments.

[0028] An embodiment of the present invention is a separator comprising a dispersion medium, a ceramic material, a one-dimensional nanomaterial, a linear hydrophilic polymer, and an adhesive. Octopus A nanoslurry for coating is provided.

[0029] The dispersion medium may be any liquid that can be used to disperse materials, and the water content of the dispersion medium may be 90 wt% or more, and may further include dispersion media such as ethanol, acetone, and N-methylpyrrolidone.

[0030] That is, the water content may be 90wt%, 92wt%, 93wt%, 95wt%, 98wt%, 99wt%, or 100wt%.

[0031] In some of the solutions, when the water content in the dispersion medium is not 100wt%, it is indicated that in addition to water, other solvents are also introduced into the dispersion medium, whereby the surface tension of the mixed solvent can be greatly reduced due to the introduction of other solvents into the water, and the reduction in surface tension contributes to further improving the dispersion uniformity of the ceramic material, the one-dimensional nanomaterial, and the linear hydrophilic polymer, thereby allowing the linear hydrophilic polymer to be more fully connected and contacted with the ceramic material and the one-dimensional nanomaterial, thus better solving the problem of aggregation of ceramic particles.

[0032] The ceramic material includes at least one of alumina, silicon oxide, titanium oxide, magnesium hydroxide, boehmite, etc., and the particle size of the ceramic material (e.g., alumina) is within the range of 5 to 500 nm. When the particle size is within this range, the surface energy of the ceramic material is large, so that the material is very prone to aggregation, destabilizing the slurry. In the embodiment of the present invention, a one-dimensional nanomaterial and a linear hydrophilic polymer are introduced to reduce the tendency of aggregation that occurs under these conditions. In comparison, the ceramic material used in the related art is Particle size Since is typically greater than 600 nm, the technical problem of agglomeration does not typically occur, and both the discovery and resolution of the agglomeration problem is an improvement of one embodiment of the present invention.

[0033] The one-dimensional nanomaterials may be understood as nanowires, nanotubes, or nanorods, and may include, for example, at least one of nanocellulose, carbon nanotubes, aramid nanofibers, and polyimide nanofibers.

[0034] In other words, the present invention can reduce the surface roughness of the formed coating by introducing one-dimensional nanomaterials into a ceramic material and reducing the surface energy of the material.

[0035] The mass ratio of the one-dimensional nano material to the ceramic material is within the range of 0.01% to 20%. For example, the mass ratio may be 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%. The selected material can be changed and the corresponding value selected according to the test. In one example, the mass ratio of the one-dimensional nano material to the ceramic material is within the range of 12% to 20%.

[0036] Furthermore, one-dimensional nanomaterials account for 1% to 20% of ceramic materials.

[0037] Based on research into the slurry state, it can be found that the selection of the mass of the one-dimensional nanomaterial has a certain correlation with the final slurry state (e.g., viscosity) (this correlation will be described later with reference to Table 1), and thus the present invention creatively discovers and utilizes this finding, selecting the mass ratio of the one-dimensional nanomaterial to the ceramic material in the range of 0.01% to 20%, effectively ensuring that the slurry can be easily applied.

[0038] The diameter of the one-dimensional nanomaterial is within the interval of 1 to 50 nanometers, and the length of the one-dimensional nanomaterial is within the interval of 100 to 1000 nanometers.

[0039] The linear hydrophilic polymer acts as a bridge between the 1D nanomaterial and the ceramic material, completely binding them together, further reducing the tendency of the ceramic material to aggregate, and further reducing the surface roughness of the formed coating. The introduction of the linear hydrophilic polymer can also contribute to avoiding the settling of the slurry and improving the stability of the slurry. A comparison of the specific performance will be described later with reference to Table 1.

[0040] In a further example, the mass ratio of the linear hydrophilic polymer to water in the dispersion medium may be within the interval of 0.01% to 0.1%, such as 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%.

[0041] The molecular weight of the linear hydrophilic polymer may be within the interval of 1000 g / mol to 10000 g / mol, for example, 1000 g / mol, 2000 g / mol, 3000 g / mol, 4000 g / mol, 5000 g / mol, 6000 g / mol, 7000 g / mol, 8000 g / mol, 9000 g / mol, or 10000 g / mol.

[0042] The linear hydrophilic polymer includes an amine hydrophilic polymer, examples of which include, but are not limited to, at least one of polyacrylamide and polyethyleneimine.

[0043] Regarding the use of amine hydrophilic polymers, the principle of their functioning is as follows. Dangling bonds are formed due to defects on the surface of ceramic materials, but amines (-NH-) have lone pairs of electrons and easily bond with dangling bonds on the surface of ceramic materials, so they have a very good affinity with ceramic materials. This makes amine hydrophilic polymers One end Ceramics materialThe other end of the amine hydrophilic polymer is a non-polar carbon-based molecular chain, which has poor compatibility with polar water, and therefore the ceramics containing the amine hydrophilic polymer are material After the carbon-containing one-dimensional nanomaterial is introduced, the carbon-containing molecular chains on the amine hydrophilic polymer have a high affinity with the carbon-containing molecular chains on the one-dimensional nanomaterial, so that the ceramic material The amine polymer-1D nanomaterial structure is formed, and the hydrophilic functional groups on the 1D nanomaterial form a highly stable network structure in water, which greatly improves the stability of the structure in water. As a result, the amine hydrophilic polymer can act as a dispersant. In one embodiment, a linear hydrophilic polymer is attached to the 1D nanomaterial.

[0044] Based on the research on the slurry state, it can be found that the linear hydrophilic polymer is correlated with the state of the dispersion liquid (the correlation will be described later with reference to Table 1), and thus the present invention creatively discovers and utilizes this discovery, and selects the mass ratio of the linear hydrophilic polymer to the water in the dispersion medium to be in the interval range of 0.01% to 0.1%, which can avoid the settling of the slurry and ensure the stability of the slurry, while effectively playing the role of reducing the aggregation of the ceramic material.

[0045] The adhesive may be any material capable of performing an adhesive function, including, for example, at least one of polyvinyl alcohol, lithium polyacrylate, sodium carboxymethyl cellulose, and styrene butadiene rubber.

[0046] Furthermore, the mass ratio of the adhesive to the ceramic material may be in the range of 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.

[0047] In this regard, if there is too much adhesive (e.g., the mass ratio of adhesive to ceramic material is greater than 10%), SeparatorThe pores become clogged, which affects the transport rate of lithium ions, but conversely, if the amount of adhesive is too small (for example, if the mass ratio of the adhesive to the ceramic material is less than 1%), the ceramic material and the one-dimensional nanomaterial are easily peeled off from the separator. Therefore, by selecting the range of 1% to 10%, the transport rate and adhesive performance can be effectively achieved at the same time. In order to obtain the above-mentioned nanoslurry, an embodiment of the present invention further provides a nanoslurry preparation method for preparing the above-mentioned nanoslurry, and referring to FIG. 1, the preparation method includes steps S11 to S14, In S11, a ceramic material is dispersed in a dispersion medium to obtain a ceramic dispersion liquid; In S12, a one-dimensional nano material is dispersed in the ceramic dispersion to obtain a predetermined dispersion; In S13, a linear hydrophilic polymer is added to the predetermined dispersion, and the predetermined dispersion is Disperse and stabilize to obtain a desired solution, In S14, an adhesive is added to the predetermined solution to obtain a nanoslurry.

[0048] In a specific example of step S11, the ceramic material can be sufficiently dispersed in the dispersion medium, and the water content in the dispersion medium is 90 wt% or more. For example, at least one of high-speed stirring, high-pressure homogenization, sand polishing dispersion, etc. can be used as the dispersion method, and the ceramic material is uniformly dispersed in the dispersion medium to form a ceramic dispersion. In one example, the concentration of the ceramic material in the ceramic dispersion may be 0.01 to 50 wt%.

[0049] In a specific example of step S12, the one-dimensional nanomaterial is added to the ceramic dispersion, and then the one-dimensional nanomaterial is dispersed again by at least one of high-speed stirring, high-pressure homogenization, sand polishing dispersion, etc., to thoroughly and uniformly mix the ceramic material with the one-dimensional nanomaterial. The dispersion method in step S11 may be the same as or different from the dispersion method in step S12.

[0050] In a specific example of step S13, the linear hydrophilic polymer is added, followed by homogenization and centrifugation at a predetermined pressure (e.g., 500-2000 bar). Location Stir at a constant speed (e.g. 3k-50kr / min) At least one of The linear hydrophilic polymer can also be attached to the one-dimensional nanomaterial by dispersing the linear hydrophilic polymer in a predetermined dispersion to which the linear hydrophilic polymer has been added.

[0051] The adhesion is based on the ability of the linear hydrophilic polymer itself to complete the adhesion upon dispersion.

[0052] In some cases, due to the huge surface energy, the ceramic material and one-dimensional nanomaterial particles in the dispersion exist as aggregates, and it is difficult for ordinary polymers to penetrate into these aggregates. The linear hydrophilic polymer selected by the present invention has linear characteristics and has low resistance to penetrating into the aggregates, while when an amide material is selected as the linear hydrophilic polymer, the amide has strong polarity and is very compatible in water, so the linear hydrophilic polymer can easily penetrate into the aggregates together with water, and the polar interaction can tightly coat the nanomaterial surface, and the aggregates can be destroyed by strong external forces (high pressure, high speed stirring, etc.) to disperse stably in water.

[0053] In the specific example of step S14, an adhesive may be added to the predetermined solution obtained after step S13, and in some examples, an auxiliary may be added after this. To facilitate the explanation of the role of the various features in the above specific examples, the following data obtained by testing is described.

[0054] [Table 1-1] [Table 1-2]

[0055] As can be seen from Comparative Example 2 and Comparative Example 3, when no linear hydrophilic polymer is added, the slurry cannot exist stably, and the surface roughness of the separator after coating is more than 1000 nm, which is far greater than the roughness of the base film (450 nm), but is still smaller than the case where no linear hydrophilic polymer and one-dimensional nanomaterial are added at all (Comparative Example 1). is In the case where the linear hydrophilic polymer is added, the surface roughness of the separator reaches 400 nm. As is clear from a comparison with Examples 1 and 3 to 5, this indicates a correlation between the roughness and the presence or absence of the linear hydrophilic polymer, and the addition of an appropriate amount of the linear hydrophilic polymer can contribute to a reduction in the roughness.

[0056] As is clear from a comparison between Example 1 and Comparative Example 5, when nanocellulose is not added, the slurry is prone to settling, and the surface roughness of the applied separator is as high as 1200 nm. As is clear from a comparison between Example 1 and Comparative Example 4, when the content of nanocellulose is too high (25%), the viscosity of the slurry is too high to be applied. In view of this, the mass ratio of the one-dimensional nanomaterial to the ceramic material is set to 0.01% to 20% in the examples of the present invention.

[0057] Other 1D nanomaterials and linear hydrophilic polymers have a similar function, i.e., reducing surface roughness (Examples 3, 4, and 5), provided that they are within the appropriate range.

[0058] The main cause of the above-mentioned roughness problem is that when the dimensions of the ceramic material are small (particle size 5-500 nm), the ceramic material has a very large surface energy, which makes it very easy to aggregate, making the slurry unstable and causing the roughness of the surface of the applied separator to rise sharply. In order to reduce the surface energy, it can be achieved by adding a hydrophilic polymer, and by binding the hydrophilic polymer with the surface of the ceramic material, the affinity with water can be strengthened, thereby reducing the surface energy. As shown in Comparative Examples 5 and 6, when the mass ratio of linear hydrophilic polymer to water is set to 0.01-0.1%, the surface roughness of the separator is better than that of Comparative Example 1, but since no one-dimensional nanomaterial is added, the stability is still poor and the roughness is still large.

[0059] Comparing Example 1 with Example 6, Example 5 with Example 7, and Example 3 with Example 8, it is clear that when the content of water in the dispersion medium is not 100 wt%, other solvents are introduced into the water, so that the surface roughness of the separator can be effectively reduced. The reason for this is that the surface tension of the mixed solvent (i.e., the dispersion medium) is greatly reduced due to the introduction of other solvents. After the one-dimensional nanomaterial, ceramic material, and linear hydrophilic polymer are added, the dispersion uniformity of the ceramic material, one-dimensional nanomaterial, and linear hydrophilic polymer can be further improved, so that the problem of aggregation of ceramic particles is better solved and the surface roughness of the coating is further reduced.

[0060] In addition, in the implementation process of the above examples and comparative examples, a PE base film with a thickness of 11 μm, a pore size of 40 nm, and a porosity of 42% is selected as the base film used, and therefore the above technical effects realized by the above examples and comparative examples are realized by coating using the same (or similar) base film.

[0061] Corresponding to the above-mentioned nanoslurry and its preparation method, an embodiment of the present invention provides a battery separator, including a base film and a coating, the coating is formed by applying a predetermined nano-slurry to at least one surface of the base film; The predetermined nanoslurry is Octopus Alternatively, the predetermined nanoslurry is a nanoslurry prepared by the above-mentioned method for preparing a nanoslurry.

[0062] Further, an embodiment of the present invention provides a battery separator comprising a base film and a coating, the coating comprising a ceramic material, a one-dimensional nanomaterial, and a linear hydrophilic polymer, the mass ratio of the one-dimensional nanomaterial to the ceramic material being within the range of 0.01% to 20%, the particle size of the ceramic material being within the range of 5 to 500 nm, and the linear hydrophilic polymer being attached to the one-dimensional nanomaterial and connected to the ceramic material.

[0063] Any technical terms, technical means, technical effects and optional embodiments of the present invention can be understood with reference to the relevant descriptions in the preceding paragraphs.

[0064] Based on the above battery separator, referring to FIG. 2, an embodiment of the present invention further provides a method for manufacturing a battery separator, the method including: In S21, the nano-slurry is applied to a base film to form a coating on the base film; In S22, the base film with the coating is dried to obtain a battery separator.

[0065] In a specific example of step S21, the slurry is applied to a base film by at least one method such as microgravure roll coating, spray coating, dip coating, extrusion coating, etc., and then dried to obtain a ceramic material composite battery separator. The application may be one-sided application or two-sided application, thereby forming a coating on one or both sides.

[0066] An embodiment of the present invention further provides a battery comprising a battery separator according to the above optional solution.

[0067] In the description of this specification, the use of terms such as "one embodiment," "one example," "specific implementation process," "one example," and the like means that the specific features, structures, materials, or characteristics described with reference to the example or example are included in at least one example or example of the present invention. In the present specification, general expressions of the above terms do not necessarily refer to the same example or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more examples or examples.

[0068] Finally, it should be noted that the above embodiments are for illustrating the technical solutions of the present invention, but are not intended to limit the same. The present invention will be described in detail with reference to the above embodiments. However, those skilled in the art may still modify the technical solutions described in the above embodiments or make equivalent substitutions for some or all of the technical features thereof, and such modifications or substitutions shall not depart from the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A nanoslurry for separator surface coating, comprising a dispersion medium, a ceramic material, a one-dimensional nanomaterial, a linear hydrophilic polymer, and an adhesive, wherein the mass ratio of the one-dimensional nanomaterial to the ceramic material is within the range of 0.01% to 20%, the water content in the dispersion medium is 90 wt % or more, and the particle diameter of the ceramic material is within the range of 5 to 500 nm.

2. The nanoslurry of claim 1 , wherein the linear hydrophilic polymer is attached to the one-dimensional nanomaterial and links to the ceramic material.

3. The nanoslurry according to claim 1, characterized in that the mass ratio of the linear hydrophilic polymer to water in the dispersion medium is within the interval range of 0.01% to 0.1%, and the molecular weight of the linear hydrophilic polymer is within the interval range of 1000 g / mol to 10000 g / mol.

4. 10. The nanoslurry of claim 1, wherein the linear hydrophilic polymer comprises an amine hydrophilic polymer.

5. The amine hydrophilic polymer is 5. The nanoslurry of claim 4, comprising at least one of polyacrylamide and polyethyleneimine.

6. 2. The nanoslurry of claim 1, characterized in that the diameter of the one-dimensional nanomaterial is in the interval range of 1 to 50 nanometers and the length of the one-dimensional nanomaterial is in the interval range of 100 to 1000 nanometers.

7. The nanoslurry according to any one of claims 1 to 6, characterized in that the mass ratio of the adhesive to the ceramic material is in the interval range of 1% to 10%.

8. The adhesive is The nanoslurry according to any one of claims 1 to 6, characterized in that it comprises at least one of polyvinyl alcohol, lithium polyacrylate, sodium carboxymethyl cellulose, and styrene butadiene rubber.

9. A method for preparing the nanoslurry according to any one of claims 1 to 8, comprising the steps of: A step of dispersing a ceramic material in a dispersion medium having a water content of 90 wt % or more to obtain a ceramic dispersion; Dispersing a one-dimensional nanomaterial in the ceramic dispersion to obtain a predetermined dispersion; adding a linear hydrophilic polymer to said predetermined dispersion to obtain a predetermined solution; and adding an adhesive to the predetermined solution to obtain a nanoslurry.

10. After adding a linear hydrophilic polymer to the given dispersion, the preparation method further comprises: The preparation method according to claim 9, further comprising the step of dispersing the predetermined dispersion to which the linear hydrophilic polymer has been added by homogenization at a predetermined pressure and / or stirring at a predetermined speed to attach the linear hydrophilic polymer to the one-dimensional nanomaterial.

11. A battery separator, comprising a base film and a coating; The coating is formed by applying a predetermined nano-slurry to at least one surface of the base film; A battery separator, characterized in that the predetermined nanoslurry is a nanoslurry according to any one of claims 1 to 8 or a nanoslurry prepared by the preparation method according to claim 9.

12. A battery separator comprising a base film and a coating, the coating comprising a ceramic material, a one-dimensional nanomaterial, and a linear hydrophilic polymer, the mass ratio of the one-dimensional nanomaterial to the ceramic material being within the range of 0.01% to 20%, the particle size of the ceramic material being within the range of 5 to 500 nm, and the linear hydrophilic polymer being attached to the one-dimensional nanomaterial and connected to the ceramic material.

13. A battery comprising a battery separator according to claim 11 or 12.

Citation Information

Patent Citations

  • Ceramic diaphragm and preparation method and application thereof

    CN105529425A

  • Ceramic separation membrane, lithium ion battery, and preparation methods of ceramic separation membrane and lithium ion battery

    CN107799702A

  • Separator and battery

    JP2010205719A

  • Coating liquid, porous film, lithium ion battery, method of producing coating liquid, method of producing porous film, and method of producing lithium ion battery

    JP2023040759A

  • Separator for rechargeable battery and rechargeable lithium battery including the same

    US20190051879A1